The Influence of Discipline and Work Environment on Employees’ Performance - Putra, Septa; Liswani, Edy (Jurnal Ilmu Manajemen, 2020)
This study aimed to determine whether or not there was an influence of work discipline and work environment on the employees’ performance in regional division III Palembang PT. Kereta Api Indonesia (Persero). The samples taken were 53 respondents. The data used was was primary data. The method of collecting data was through questionnaires. The data anaysis used was qualitative and quantitative analysis. The analysis technique used multiple linear regression. The result of multiple linear regression analysis showed the regression equation: Y = 1.348 + 0.262 X1 + 0.378 X2. The result of simultaneous hypothesis test result proved that there was an influence of work discipline and work environment on employee performance.The results of hypothesis testing partially proved that there was an influence of work discipline and work environment on employee performance. The coefficient of determination test result showed that the variables of work discipline and work environment were able to contribute to the fluctuation of changes that occurred in employees’ performance, with a large contribution caused was 36.8%